2020
DOI: 10.1177/0734242x20914731
|View full text |Cite
|
Sign up to set email alerts
|

In search of the optimal inoculum to substrate ratio during anaerobic co-digestion of spent coffee grounds and cow manure

Abstract: The inoculum to substrate (I:S) ratio is a crucial operating parameter during the start-up period of anaerobic digestion (AD) processes and this ratio shows high differentiation with respect to substrate composition. While spent coffee grounds (SCG) have started to gain attraction in AD as a co-substrate due to their vast production and promising methane potential, there is still not enough information on the operative environment of SCG-based biogas reactors. This study investigated the optimal I:S ratio duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Five AcoD combinations and two inocula were assessed to investigate the mesophilic BMP performance of the local waste. The inoculum-to-substrate ratio I:S did not show biomass inhibition [ 35 ], perhaps due to the high organic content of the inoculum. The reactors were running for 60 days to assure the total degradation of the waste under the selected experimental conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Five AcoD combinations and two inocula were assessed to investigate the mesophilic BMP performance of the local waste. The inoculum-to-substrate ratio I:S did not show biomass inhibition [ 35 ], perhaps due to the high organic content of the inoculum. The reactors were running for 60 days to assure the total degradation of the waste under the selected experimental conditions.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Orfanoudaki et al [28], who studied the anaerobic co-digestion of SCG and pig slurry, found a maximum methane production of 357 mL CH 4 /g VS. In another study [48], a mixture of SCG and cow manure at 1:1 (VS basis) led to 225 mL CH 4 /g VS.…”
Section: Overall Mass Balancementioning
confidence: 96%
“…Nonetheless, this accumulation of VFAs does not always exemplify a pH drop, owing to the buffer capacity of some waste forms. There is an excess of alkalinity in manure, denoting that the VFA growth shall surpass a certain point before it can be determined as a significant change in pH [81]. When the pH in the reactor drops, the concentration of VFAs is possibly very high, and the process may previously have been affected [82].…”
Section: Anaerobic Digestion Phmentioning
confidence: 99%